Struktur Percakapan Host Utama Dalam Talk Show Oshareizumu - Elsy fitriyany; Yanti Hidayati; Andi Abd Khaliq Syukur (Universitas Diponegoro, 2024)
This research analyzes the conversational structure of the main host in the talk show